"Castration Anxiety" Revisited: Especially "Female Castration Anxiety". Issue 1 (2nd January 2018) - Balsam, Rosemary H.
ABSTRACT: I find the term castration anxiety a still relevant and important key body fearful fantasy in males, especially expressing fear of the father; as is female castration anxiety an equivalent key fear of the ablation of the sexual and reproductive organs of females, especially by the avenging mother. Freud's and his followers' version of the female anxiety, however, has repetitively been shown to be askew since the 1930s, yet it keeps appearing again, as if still worthy of serious argument. To demonstrate its utter blindness to an emotional or imaginative appreciation of female body reproductive functioning, a detailed critique is offered of the once classic paper, "The Body as Phallus" by Bertram Lewin (1933). I recommend that a straightforward sense of female castration is helpful in exploring female body anxieties as a more defined bodily referent than can be encompassed by separation anxieties that are currently more popular.